2019
DOI: 10.1016/j.ymthe.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Engineered DNA Vaccination against Follicle-Stimulating Hormone Receptor Delays Ovarian Cancer Progression in Animal Models

Abstract: Ovarian cancer presents in 80% of patients as a metastatic disease, which confers it with dismal prognosis despite surgery and chemotherapy. However, it is an immunogenic disease, and the presence of intratumoral T cells is a major prognostic factor for survival. We used a synthetic consensus (SynCon) approach to generate a novel DNA vaccine that breaks immune tolerance to follicle-stimulating hormone receptor (FSHR), present in 50% of ovarian cancers but confined to the ovary in healthy tissues. SynCon FSHR D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…A greater proportion of FSHR only complexes would thus program the cell fate toward FSHR/cAMP-dependent death, a finding well described in the literature [5][6][7]9,[55][56][57][58][59] but neglected for a long-time due to the lack of evidence on the pro-apoptotic action of FSH in vivo. Indeed, FSH action is commonly associated with 32 proliferative events, follicular growth being the physiological example, and as suggested by the presence of FSHR in pathological contexts characterized by uncontrolled cell growth, such as cancer 28 or endometriosis 29 , which indicated FSHR as a target of anti-cancer drugs 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A greater proportion of FSHR only complexes would thus program the cell fate toward FSHR/cAMP-dependent death, a finding well described in the literature [5][6][7]9,[55][56][57][58][59] but neglected for a long-time due to the lack of evidence on the pro-apoptotic action of FSH in vivo. Indeed, FSH action is commonly associated with 32 proliferative events, follicular growth being the physiological example, and as suggested by the presence of FSHR in pathological contexts characterized by uncontrolled cell growth, such as cancer 28 or endometriosis 29 , which indicated FSHR as a target of anti-cancer drugs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian granulosa cells express both FSHR and GPER 25 modulating a network of proliferative signals 26,27 fundamental for regulating gametogenesis 21 . Consistent with its impact on cell growth, FSHR expression was found in pathological contexts characterized by uncontrolled cell proliferation, such as tumors 28 or endometriosis 29 , suggesting that it could be a target for still outstanding anti-cancer therapies 30 . Similarly, GPER expression has been described in several tumor cells 31 , including breast, endometrium and ovary 32 , where it may cooperate with FSHR in inducing uncontrolled cell proliferation 27,33 .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…DNA plasmids co-formulated with hyaluronidase have been shown to increase in vivo expression. 20,39,40 Despite variable expression levels, the ability of the different antibodies to bind to ZIKV envelope is similar at normalized serum concentrations. An area of concern for antibody therapies for flaviviruses, particularly dengue virus, is the potential for antibody-dependent enhancement (ADE) of infection where sub-neutralizing levels of antibodies can mediate greater levels of infection by allowing uptake of virus into cells expressing the Fc receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid DNA vaccination provides a simple and accessible approach to immune therapy, generating an activated immune response to tumor-associated antigens in vivo. Vaccination with highly optimized DNA cancer vaccines and delivered by the CELLECTRA R electroporation (EP) device for cancer has been highly effective in the preclinical space (7)(8)(9)(10)(11) and results from a phase 2b clinical trial testing VGX-3100 for patients with cervical intraepithelial neoplasia showed this therapy to be safe, efficacious, and immunogenic (12). It has been well-documented that the specific targeting of immune cells by molecular adjuvants increases the immune response to viral associated antigens (13)(14)(15)(16), thus the potential exists to further increase the magnitude of the vaccine-elicited responses against tumor-associated antigens (TAAs) enabling tumor control.…”
Section: Introductionmentioning
confidence: 99%